Formal organizations and interstitial spaces: Catalysts, complexity, and the initiation of cross-field collaboration. (February 2021) - Villani, Elisa; Phillips, Nelson
Interstitial spaces are informal settings where interactions among actors from different organizational fields are more likely to succeed despite the institutional complexity that they face. Individuals acting as "catalysts" have been identified as being particularly important in the dynamics of these interstitial spaces. However, the focus to date has been on individuals interacting in interstitial spaces that have developed informally, and we know little about how formal organizations might purposefully create and manage interstitial spaces to initiate cross-field interaction. Using data from a study of six organizations involved in technology transfer activities between universities and industry in Italy, we explore how formal organizations use interstitial spaces to encourage cross-field collaboration and identify the set of formal and informal activities employed by catalysts to manage the complexity that arises. In addition, our analysis identifies two activities implemented at the organizational and field level by the formal organizations to support the interstitial spaces. Based on these results, we develop a model of the management of interstitial spaces by formal organizations.